SELECTION OF FEED SUPPLIER IN SEA FISH CULTIVATION USING ANALYTICAL HIERARCHY PROCESS (AHP) METHOD - Dasril Aldo; Muhamad Apri (LPPM Nusa Mandiri, 2020)
The problem that often occurs in the cultivation of seawater fish is the lack of efficiency in determining the right supplier, usually the fish culture simply selects the supplier, namely by contacting the supplier asking for the help of sea fish needed and the price according to the order or not. If appropriate, the company issues a purchase order. Receiving results is not optimal because it does not consider other considerations such as quality, price, service, delivery time, and guarantee. This study aims to overcome these problems and make it easier for farmers to select appropriate suppliers of marine fish feed. Analytical Hierarchy Process (AHP) method used as a support in this study for the analysis of suppliers of data obtained from Batam Aquaculture Fisheries Center (BPBL) Batam with contributions in the form of Quality, Price, Service, Delivery, Delivery, and Guarantee. The stages of this method are determining the value of pairs, making the value of the criteria, Calculating the Eigen Value of the Principle, Calculating the Eigen Value of the Principle of the final value in making decisions. From the evaluation of the 5 supplier data, the results obtained rank rankings of each supplier with Supplier_003 as rank 1 with a value of 4.25 and Supplier_002 as rank 2 with value. 3.99 is accepted as a decision of Supplier_003 as the selected supplier and Supplier_002 Reserve supplier, while other suppliers are not selected. With these results, the decision support system using the AHP method can be applied as a supplier of fish suppliers at the Batam Aquaculture Fisheries Center (BPBL)